Non-combustible cable and preparation method thereof

By adopting multi-layer cable structure and high-temperature processed glass powder filling technology, the problem of traditional cables burning and releasing toxic gases in fires is solved, the fireproof performance and safety of non-combustible cables are achieved, and modern fire safety requirements are met.

CN119340008AInactive Publication Date: 2025-01-21HUIZHOU JINLONGYU CABLE IND DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411378279.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cables are prone to burn when a fire occurs, release toxic gases, threaten the safety of life and property, and cannot meet the high requirements for fire safety of modern buildings and industrial facilities.

Method used

It adopts a multi-layer cable structure, with the outer layer wrapping the inner layer. The structure consists of conductors, calcined mica tapes, ceramic silicone tapes, double-sided water-blocking tapes, ceramic fibers, dense fiberglass tapes, copper sheaths, glass powder and copper sheaths wrapped again. Set consists of. Glass powder is composed of silicate, borate and oxide, prepared through high-temperature melting and water quenching, and is filled in the outer layer of the cable to enhance fire resistance.

Benefits of technology

It realizes that the cable will not burn in a fire, prevents the release of toxic gases, ensures the reliability and safety of power supply, and complies with strict fire safety standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340008A_ABST
    Figure CN119340008A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cables, in particular to a non-combustible cable and a preparation method thereof. The cable structurally comprises a conductor, a calcined mica tape, a ceramic silica gel tape, a double-sided water-blocking tape, ceramic fibers, a dense glass fiber tape, a first copper sheath, glass powder and a second copper sheath from inside to outside in sequence, the section of the cable is circular; the glass powder is prepared from the following components in parts by weight: 20 to 25 parts of silicate, 10 to 13 parts of borate and 18 to 20 parts of oxide. According to the invention, a plurality of protective materials have a synergistic effect, and the calcined mica tape, the ceramic silica gel tape, the ceramic fiber and the dense glass fiber tape enhance the fire resistance of the cable; the double-sided water-blocking tape can prevent water from invading; the copper sheath plays a good role in mechanical protection and grounding; the glass powder can further improve the flame retardant property of the cable. The non-combustible cable has remarkable advantages in the aspects of fire prevention, water prevention, mechanical strength and the like, and is suitable for places with relatively high requirements on safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, and in particular to a non-combustible cable and a preparation method thereof. Background Art

[0002] At present, with the continuous growth of electricity demand, the use of cables is becoming more and more widespread. However, traditional cables are easy to burn and release toxic gases when a fire occurs, posing a serious threat to people's lives and property safety.

[0003] ①Disadvantages of traditional cables

[0004] Traditional cables are usually composed of an insulation layer and a conductor. The insulation layer is mostly made of combustible materials, such as polyethylene and polyvinyl chloride. In the event of a fire, these combustible materials are easy to burn, releasing a large amount of toxic gas and smoke, which not only threatens the life safety of personnel, but also hinders fire fighting. In addition, the burning process of traditional cables may also cause the fire to spread and expand the scope of the fire.

[0005] ②Fire safety requirements

[0006] With the continuous development of modern buildings and industrial facilities, the requirements for fire safety are getting higher and higher. In some important places, such as hospitals, schools, shopping malls, high-rise buildings, subways, etc., once a fire occurs, it is necessary to ensure the reliability and safety of power supply to ensure the normal operation of key functions such as personnel evacuation and fire fighting equipment. Non-combustible cables can maintain the integrity of the circuit in a fire and provide the necessary power support for fire fighting and emergency rescue.

[0007] ③ Promotion of laws and regulations and standards

[0008] In order to improve the fire safety of electrical systems, countries have formulated strict regulations and standards, and put forward clear requirements for the flame retardant and non-combustible properties of cables. For example, in some countries and regions, it is stipulated that non-combustible cables or flame retardant cables must be used in specific places. The introduction of these regulations and standards has prompted cable manufacturers to continuously develop and produce cable products with higher fire resistance.

[0009] Therefore, developing a non-flammable cable has important practical significance. Summary of the invention

[0010] The object of the present invention is to provide a non-combustible cable and a preparation method thereof, so as to solve the problem that the traditional cable is easy to burn and release toxic gas when a fire occurs.

[0011] In order to achieve the above object, the present invention adopts the following technical solution:

[0012] A non-combustible cable has a multi-layer cable structure, wherein the outer layer wraps the inner layer, and the cable structure comprises, from the inside to the outside, a conductor, a calcined mica tape, a ceramic silicone tape, a double-sided water-blocking tape, ceramic fiber, a dense glass fiber tape, a first copper sheath, glass powder, and a second copper sheath; the cross-sectional shape of the cable is circular; the glass powder comprises the following components by weight: 20 to 25 parts of silicate, 10 to 13 parts of borate, and 18 to 20 parts of oxide.

[0013] Preferably, the conductor is a round conductor formed by twisting and pressing multiple special-shaped single-crystal copper wires; the thickness of the calcined mica tape is 0.14 mm, and it is wrapped in 5 layers on the outer layer of the conductor, with an overlap rate of each layer of 15%-25%; the thickness of the ceramic silicone tape is 0.5 mm, and it is wrapped in 1 layer on the outer layer of the calcined mica tape, with an overlap rate of 15%-25%; the thickness of the double-sided water-blocking tape is 0.3 mm, and it is wrapped in 1 layer on the outer layer of the ceramic silicone tape, with an overlap rate of 20%-30%.

[0014] Preferably, the thickness of the ceramic fiber is 0.5mm, and one layer of it is wrapped around the outer layer of the double-sided water-blocking tape, with an overlap rate of 25%-45%; the thickness of the dense glass fiber tape is 0.2mm, and one layer of it is wrapped around the outer layer of the ceramic fiber, with an overlap rate of 10%-15%; the thickness of the first copper sheath is 0.5mm, and the corrugation depth is 1.5mm, and it is arranged on the outer layer of the dense glass fiber tape; the thickness of the glass powder is 1.8mm±0.10mm, and the glass powder is filled in one layer on the outer layer of the first copper sheath; the thickness of the second copper sheath is 0.8mm, and the corrugation depth is 1.0mm, and it is arranged on the outer layer of the glass powder.

[0015] Preferably, the silicate is one or more of orthoclase, talc, and asbestos; the borate is one or more of borax, borax, and colemanite; and the oxide is one or more of titanium dioxide, manganese dioxide, and ferric oxide.

[0016] Silicate is selected from one or more of orthoclase, talc and asbestos, as follows:

[0017] 1. Orthoclase (KAlSi 3 O 8 )

[0018] The main components include potassium (K), aluminum (Al), silicon (Si) and oxygen (O). It is usually flesh-red, light yellow-white, etc., with a hardness of about 6 and a glassy luster. It is an important rock-forming mineral used in industries such as ceramics and glass.

[0019] 2. Talc (Mg 3 Si 4 O 10 (OH)2 )

[0020] Contains magnesium (Mg), silicon, oxygen and hydrogen (H). White or various light colors, low hardness, and greasy. Can be used as refractory materials, papermaking, rubber fillers, etc.

[0021] 3. Asbestos (mainly serpentine asbestos, Mg 3 Si 2 O 5 (OH) 4 )

[0022] It is composed of magnesium, silicon, oxygen and hydrogen. It is fibrous and has high fire resistance, electrical insulation and thermal insulation properties, but its use is restricted due to its potential harm to human health.

[0023] The borate is selected from one or more of borax, borax and colemanite, as follows:

[0024] 1. Magnesium iron ore (Mg, Fe) 2 Fe[BO 3 ]O 2 )

[0025] It contains magnesium (Mg), iron (Fe), boron (B) and oxygen. It is usually black or black-green in color and can be used as a source of boron ore for the production of boron compounds.

[0026] 2. Borax (Na 2 B 4 O 7 10H 2 O)

[0027] The main components are sodium (Na), boron and oxygen, as well as crystal water. Colorless translucent crystals or white crystalline powder can be used in industries such as glass, ceramics, and metallurgy, and are also used in medicine, agriculture, and other fields.

[0028] 3. Colemanite (Ca 2 B 6 O 11 ·5H 2 O)

[0029] Contains calcium (Ca), boron, oxygen and crystal water. White or off-white, it is one of the important boron ores and is used to extract the boron element.

[0030] The oxide is selected from one or more of titanium dioxide, manganese dioxide, and ferric oxide, as follows:

[0031] 1. Titanium dioxide (TiO 2 )

[0032] It is composed of titanium (Ti) and oxygen. It is a white solid with a high refractive index. It is widely used as a white pigment in coatings, plastics, papermaking and other industries. It also has important applications in fields such as photocatalysis.

[0033] 2. Manganese dioxide (MnO 2 )

[0034] Contains manganese (Mn) and oxygen. Black or brownish black powder, commonly used as a catalyst, oxidant, depolarizer for dry cell batteries, etc.

[0035] 3. Ferrous oxide (Fe 2 O 3 )

[0036] It is composed of iron and oxygen. It is red to reddish brown in color and is an important pigment. It is also used in industrial fields such as iron smelting.

[0037] A method for preparing a non-combustible cable as described above comprises the following steps:

[0038] A. Conductor preparation: Use special-shaped single crystal copper wire, and twist and compress multiple special-shaped single crystal copper wires to form a round conductor;

[0039] B. Wrapping of each layer of materials: in the aforementioned order, the calcined mica tape, the ceramic silicone tape, the double-sided water-blocking tape, the ceramic fiber, the dense glass fiber tape and the first copper sheath are tightly wrapped on the outer layer of the conductor in sequence to obtain a semi-finished product B;

[0040] C. Filling of glass powder: filling the outer layer of the semi-finished product B obtained in step B with glass powder evenly to obtain a semi-finished product C;

[0041] D. Cable molding: a second copper sheath is provided on the outer layer of the semi-finished product C, and the semi-finished product C is wrapped and molded to obtain a finished cable;

[0042] The preparation method of the glass powder is as follows:

[0043] ① Raw material preparation: prepare the required raw materials, including silicates, borates, and oxides;

[0044] ② Ingredient mixing: Accurately weigh various raw materials according to the formula ratio, put the weighed raw materials into the mixing equipment, stir and mix them thoroughly to form a mixture;

[0045] ③ High temperature melting: Put the mixture into a high temperature furnace and heat it to above 1000℃ to completely melt the mixture to obtain molten glass liquid;

[0046] ④ Water quenching cooling: Take the molten glass liquid out of the furnace and quickly pour it into water for water quenching;

[0047] ⑤ Grinding and crushing: Take out the glass pieces after water quenching and put them into the grinding equipment for grinding;

[0048] ⑥ Screening and grading: The ground glass powder can be screened to obtain glass powder of the required particle size.

[0049] Preferably, the glass powder in step C is extruded by an extruder so that it can be evenly filled in the outer layer of the semi-finished product B. The specific glass powder extrusion steps are as follows:

[0050] (1) Raw material preparation: Add the manufactured glass powder into the twin-screw extruder;

[0051] (2) Extruder preheating: Heat each area of ​​the extruder to 950°C to ensure that the glass powder can be melted and extruded smoothly;

[0052] (3) Feeding: Feed the mixed raw materials into the hopper of the extruder through a feeder;

[0053] (4) Melt extrusion: The mixed raw materials are gradually melted and pushed toward the die under the action of the extruder screw, shear force and heat;

[0054] (5) Molding: The molten glass powder passes through the die of the die head and is evenly extruded on the outer layer of the semi-finished product B to form the desired shape and size;

[0055] (6) Cooling and shaping: The extruded product is quickly cooled by a cooling water trough device to solidify and shape it; (7) Traction: The cable product after cooling and shaping is pulled out of the extruder using a traction device to obtain a semi-finished product C.

[0056] Preferably, a 10-head horizontal wrapping machine is used to wrap the calcined mica tape around the outer layer of the conductor, and the tension of the calcined mica tape is stably controlled by a tension regulator during the wrapping process; a 10-head horizontal wrapping machine is used to wrap the ceramic silicone tape, double-sided water-blocking tape, ceramic fiber, and dense glass fiber tape; and the first copper sheath and the second copper sheath are produced using imported copper sheath argon arc welding equipment.

[0057] Preferably, during the high-temperature melting process in step ③, it is necessary to control the melting temperature to be not less than 1200°C, the time to be not less than 12 minutes, and the atmosphere temperature to be not less than 600°C.

[0058] Preferably, in the screening and grading in step ⑥, the ground glass powder is screened and glass powder with a particle size of 0.25 mm-0.30 mm is selected.

[0059] Preferably, the glass powder filled in the outer layer of the semi-finished product B has a stirring pressure of 14 bar and a viscosity of 690 Pa·s to 900 Pa·s before filling.

[0060] In summary, the materials used in the non-combustible cable of the present invention are all non-combustible materials, and a layer of glass powder is separately laid in the cable. This specific structure and material combination enables the cable of the present invention to pass the test requiring a total calorific value PCS ≤ 2.0 MJ / kga. For specific experimental values ​​and information, see Tables 1 and 2. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 It is a schematic diagram of the cross-sectional structure of the non-combustible cable of the present invention;

[0062] Explanation of the reference numerals: 1. conductor; 2. calcined mica tape; 3. ceramic silicone tape; 4. double-sided water-blocking tape; 5. ceramic fiber; 6. dense glass fiber tape; 7. first copper sheath; 8. glass powder; 9. second copper sheath. DETAILED DESCRIPTION

[0063] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes, but it does not constitute a limitation on the protection scope of the present invention.

[0064] Glass powder is an inorganic non-metallic material. Glass powder has the characteristics of high hardness, high transparency, and chemical corrosion resistance. In industry, glass powder is usually used in coatings, inks, plastics, rubber and other fields to increase hardness, improve wear resistance, and improve surface gloss.

[0065] The structural design principle of the present invention is as follows:

[0066] ① When the cable encounters a fire, materials such as calcined mica tape, ceramic silicone tape, ceramic fiber and glass powder can effectively prevent the spread of flames without releasing toxic gases.

[0067] ② Double-sided water-blocking tape and copper sheath can prevent the influence of moisture and external electromagnetic interference on the cable.

[0068] ③Dense glass fiber tape and copper sheath can improve the mechanical strength of the cable, making it less likely to be damaged in a fire.

[0069] As can be seen from the above, the solution of the present invention has the following beneficial effects:

[0070] ①It has excellent fireproof performance and can effectively prevent the spread of flames when a fire occurs, protecting people’s lives and property.

[0071] ②It will not release toxic gases and is environmentally friendly.

[0072] ③It has good waterproof and electromagnetic shielding performance and can adapt to various harsh environments.

[0073] ④High mechanical strength and long service life.

[0074] Meanwhile, glass powder in the prior art cannot be processed into cables, so the present invention develops a glass powder and a processing method thereof so that it can be processed and applied to cables.

[0075] When the cable is exposed to fire, as the cable temperature rises, the sodium-containing glass will decompose sodium oxide at high temperature, and sodium oxide will react with carbon dioxide in the air at high temperature to produce sodium carbonate and other substances. Silicon dioxide will undergo structural changes at extremely high temperatures, but it is generally more stable and not easy to completely decompose into other substances.

[0076] Since the glass powder material is produced while being manufactured, the following two points should be noted during production:

[0077] ① Humidity of glass powder: The ratio of silicate, borate and oxide needs to be controlled. When the mass of silicate is greater than that of borate and oxide, the oxygen barrier material stirred out will be very dry, which will cause the glass powder to fall off during extrusion. When the mass of silicate is less than that of borate and oxide, the oxygen barrier material stirred out will be very wet, and extrusion will cause the borate and oxide to seep out.

[0078] ② The viscosity of the glass powder should be controlled at 690Pa·s~900Pa·s. The optimal formula ratio is 22:12:18 for silicate, borate and oxide. When the viscosity of the glass powder is less than 690cps, the glass powder will slip in the screw during extrusion, resulting in one cable core being larger than the other. When the viscosity of the glass powder is greater than 900cps, the pressure inside the screw will be too high during extrusion, making it impossible to extrude the glass powder.

[0079] In order to solve these two major problems, we first installed an electronic scale on the glass powder production equipment. We set the required weight on the electronic scale, so that we can accurately calculate the proportion when pouring silicate, borate and oxide. Secondly, we installed a pressure sensor system on the glass powder equipment. When the viscosity of the glass powder is not enough during the stirring process, the pressure sensor system will prompt an alarm signal until the viscosity of the glass powder meets the production requirements, so that the surface of the extruded glass powder layer is rounded and the roundness of the cable is better controlled.

[0080] The application effects of the glass powder obtained by the present invention are as follows:

[0081] 1. Forming a heat-insulating glass protective layer: Part of the glass powder is melted by heat and sealed with the metal wire to form a heat-insulating glass protective layer, which can effectively isolate heat and protect the cable from high temperature damage.

[0082] 2. Forming an inorganic glass-like oxygen-insulating layer: The outer layer of glass powder is heated and melted to form an inorganic glass-like oxygen-insulating layer, which can protect the inner layer of resin from high-temperature oxidation and maintain the integrity of the cable.

[0083] 3. React with free radicals to form refractory substances: Glass powder can react with free radicals of organic resin to form flame-retardant substances, effectively preventing the spread of fire.

[0084] 4. Forming an inorganic glass-like thermal conductive layer: After partial cooling, the glass powder will form an inorganic glass-like thermal conductive layer, which together with the sealing part will quickly conduct the heat away to prevent the cable from being damaged due to overheating.

[0085] 5. Specific application: Glass powder is usually added to cable materials as an additive to prepare cables with flame retardant properties, rather than as a separate layer structure; the present invention allows it to be processed separately and applied in cables.

[0086] See also Figure 1 The present invention provides a non-combustible cable, which has a multi-layer cable structure, in which the outer layer wraps the inner layer, and the cable structure from the inside to the outside is a conductor 1, a calcined mica tape 2, a ceramic silicone tape 3, a double-sided water-blocking tape 4, a ceramic fiber 5, a dense glass fiber tape 6, a first copper sheath 7, a glass powder 8, and a second copper sheath 9; the cross-sectional shape of the cable is circular; the glass powder 8 includes the following components by weight: 20 to 25 parts of silicate, 10 to 13 parts of borate, and 18 to 20 parts of oxide.

[0087] Specifically, the conductor 1 is a round conductor formed by twisting and pressing multiple special-shaped single-crystal copper wires; the thickness of the calcined mica tape 2 is 0.14 mm, and it is wrapped 5 layers on the outer layer of the conductor 1, with an overlap rate of 15%-25% for each layer; the thickness of the ceramic silicone tape 3 is 0.5 mm, and it is wrapped 1 layer on the outer layer of the calcined mica tape 2, with an overlap rate of 15%-25%; the thickness of the double-sided water-blocking tape 4 is 0.3 mm, and it is wrapped 1 layer on the outer layer of the ceramic silicone tape 3, with an overlap rate of 20%-30%. Specifically, the thickness of the ceramic fiber 5 is 0.5mm, and it is wrapped in one layer on the outer layer of the double-sided water-blocking tape 4, with an overlap rate of 25%-45%; the thickness of the dense glass fiber tape 6 is 0.2mm, and it is wrapped in one layer on the outer layer of the ceramic fiber 5, with an overlap rate of 10%-15%; the thickness of the first copper sheath 7 is 0.5mm, and the embossing depth is 1.5mm, and it is arranged on the outer layer of the dense glass fiber tape 6; the thickness of the glass powder 8 is 1.8mm±0.10mm, and the glass powder 8 is filled in one layer on the outer layer of the first copper sheath 7; the thickness of the second copper sheath 9 is 0.8mm, and the embossing depth is 1.0mm, and it is arranged on the outer layer of the glass powder 8.

[0088] Specifically, the silicate is one or more of orthoclase, talc, and asbestos; the borate is one or more of borax, borax, and colemanite; the oxide is one or more of titanium dioxide, manganese dioxide, and ferric oxide.

[0089] A method for preparing a non-combustible cable as described above comprises the following steps:

[0090] A. Preparation of conductor 1: using special-shaped single crystal copper wires, a plurality of special-shaped single crystal copper wires are twisted and pressed to form a round conductor, so as to ensure the conductive performance and mechanical strength of conductor 1;

[0091] B. Wrapping of each layer of materials: In the aforementioned order, the calcined mica tape 2, the ceramic silicone tape 3, the double-sided water-blocking tape 4, the ceramic fiber 5, the dense glass fiber tape 6 and the first copper sheath 7 are tightly wrapped on the outer layer of the conductor 1 in sequence to ensure that each layer of material is tightly combined to obtain a semi-finished product B;

[0092] C. Filling of glass powder 8: filling the outer layer of the semi-finished product B obtained in step B with glass powder 8 evenly to enhance the fireproof performance of the cable, thereby obtaining a semi-finished product C;

[0093] D. Cable molding: a second copper sheath 9 is provided on the outer layer of the semi-finished product C, and the semi-finished product C is wrapped and molded to obtain a finished cable, ensuring that the outer dimensions of the cable meet the requirements;

[0094] The preparation method of glass powder 8 is as follows:

[0095] ① Raw material preparation: prepare the required raw materials, including silicates, borates, and oxides;

[0096] ② Ingredient mixing: Accurately weigh various raw materials according to the formula ratio, put the weighed raw materials into the mixing equipment, stir and mix them thoroughly to form a mixture;

[0097] ③ High temperature melting: Put the mixture into a high temperature furnace and heat it to above 1000℃ to completely melt the mixture to obtain molten glass liquid;

[0098] ④ Water quenching cooling: Take the molten glass liquid out of the furnace and quickly pour it into water for water quenching. The purpose of water quenching is to quickly cool the glass liquid to form glass fragments. At the same time, the structure and performance of the glass can be improved by rapid cooling;

[0099] ⑤ Grinding and crushing: Take out the glass pieces after water quenching and put them into grinding equipment for grinding; the grinding process can be carried out by ball milling, air flow milling, etc. to grind the glass pieces into fine particles to obtain glass powder 8; according to different application requirements, control the grinding time and particle size to obtain glass powder 8 with the required particle size distribution;

[0100] ⑥ Screening and grading: The ground glass powder can be screened to obtain glass powder of the required particle size; sieves of different mesh sizes can be used for grading and screening.

[0101] As a preferred embodiment of the present invention, the filling of the glass powder 8 in step C is performed by extruding the glass powder 8 through an extruder, so that the glass powder 8 can be evenly filled in the outer layer of the semi-finished product B. The specific steps of extruding the glass powder 8 are as follows:

[0102] 1. Raw material preparation: Add the prepared glass powder 8 into the twin-screw extruder;

[0103] 2. Extruder preheating: heating each area of ​​the extruder to 950°C to ensure that the glass powder 8 can be melted and extruded smoothly;

[0104] 3. Feeding: Feed the mixed raw materials into the hopper of the extruder through a feeder;

[0105] 4. Melt extrusion: The mixed raw materials are gradually melted and pushed toward the die under the action of the extruder screw, shear force and heat;

[0106] 5. Molding: The molten glass powder 8 passes through the die of the die head and is evenly extruded on the outer layer of the semi-finished product B to form the desired shape and size;

[0107] 6. Cooling and shaping: The extruded product is quickly cooled by a cooling water tank device to solidify and shape it;

[0108] 7. Traction: Use a traction device to pull the cooled and shaped cable product out of the extruder, maintaining a certain speed and tension to obtain a semi-finished product C.

[0109] It should be noted that the specific extrusion process may vary depending on the equipment type, process parameters and product requirements. In actual operation, it is necessary to adjust and optimize according to the specific situation to ensure the smooth progress of the extrusion process and the stability of product quality.

[0110] In order to make the glass powder 8 evenly adhere to the surface of the cable core, the present invention produces the copper sheath into a corrugated type, so that the glass powder 8 is very even between the corrugations, and there is no eccentricity; because the corrugations are blocked and the corrugations can withstand most of the extrusion force, the glass powder 8 of the cable will not change too much. The height of the corrugation is designed according to the outer diameter of the cable. At the same time, by controlling the height of the corrugation, the thickness of the glass powder 8 can be better controlled. In this way, the glass powder 8 can fully achieve the purpose of oxygen isolation and heat insulation.

[0111] Specifically, a 10-head horizontal wrapping machine is used to wrap the calcined mica tape 2 around the outer layer of the conductor 1. At the same time, the tension of the calcined mica tape 2 is stably controlled by a tension regulator during the wrapping process to avoid the calcined mica tape 2 being subjected to stress during wrapping, which may cause the calcined mica tape 2 to be broken, delaminated, and have an uneven surface. A 10-head horizontal wrapping machine is used to wrap the ceramic silicone tape 3, the double-sided water-blocking tape 4, the ceramic fiber 5, and the dense glass fiber tape 6. The first copper sheath 7 and the second copper sheath 9 are produced using imported copper sheath argon arc welding equipment, which can fully fix the glass powder 8 in the gear sleeve.

[0112] Specifically, during the high-temperature melting process in step ③, it is necessary to control the melting temperature to be no less than 1200°C, the time to be no less than 12 minutes, and the atmosphere temperature to be no less than 600°C.

[0113] Specifically, in the screening and grading in step ⑥, the ground glass powder 8 is screened, and glass powder 8 with a particle size of 0.25 mm-0.30 mm is selected.

[0114] Specifically, the glass powder 8 filled in the outer layer of the semi-finished product B has a stirring pressure of 14 bar and a viscosity of 690 Pa·s to 900 Pa·s before filling.

[0115] The cable structure of the present invention is a multi-layer structure, the outer layer wraps the inner layer, and the cable structure from the inside to the outside is a conductor, a calcined mica tape, a ceramic silicone tape, a double-sided water-blocking tape, a ceramic fiber, a dense glass fiber tape, a copper sheath, glass powder, and a copper sheath. The specific arrangement is based on the following:

[0116] Conductor: It uses special-shaped single crystal copper wire, which is formed by twisting and pressing multiple special-shaped single crystal copper wires to form a round conductor. It has excellent conductivity, can reduce skin effect, reduce space occupation, improve electromagnetic compatibility, and improve heat dissipation performance. The specific advantages are as follows:

[0117] ①Excellent signal transmission performance: The entire copper rod is composed of only one crystal grain, and there is no "grain boundary" between the crystal grains. The "grain boundary" will reflect and refract the passing signal, causing signal distortion and attenuation. Single crystal copper eliminates this effect, so it has extremely high signal transmission performance, which can fundamentally improve the transmission quality and is widely used in audio and video signal transmission. For example, in the audio field, it can make the sound clearer, more realistic, and more pleasant to listen to.

[0118] ②The resistance is 8% to 13% lower than that of ordinary copper materials, and the impedance is lower, which makes the signal transmission smoother, can effectively reduce the resistance and loss in signal transmission, and improve the transmission quality of audio signals.

[0119] ③ Extraordinary machining performance: It has good plastic machining performance and extremely high toughness. Ordinary copper material breaks after 16 twists, while single crystal copper material can be twisted 116 times. This makes it easier to form and manufacture during the processing process, and can be used to make wires and parts of various complex shapes to meet the needs of different application scenarios.

[0120] ④ It has excellent corrosion resistance and can adapt to a variety of harsh environments, increasing the service life and stability of the product. It has significant fatigue resistance and reduces the possibility of breakage due to long-term use or repeated bending. It reduces casting defects such as segregation, pores, shrinkage, and impurities, and has a bright surface quality.

[0121] Forged mica tape: Use 0.14mm thick forged mica tape, wrapped in 5 layers, with an overlap rate of 15%-25%. The forged mica tape has good high temperature resistance and insulation properties, and can protect the conductor at high temperatures. The specific advantages are as follows:

[0122] ①Excellent high temperature resistance: Mica tape itself has the characteristics of high temperature resistance. After calcination, the high temperature resistance is further improved. In high temperature environment, the calcined mica tape can maintain good stability and is not easy to deform, melt or decompose. It can withstand high temperatures and ensure the normal operation of the cable under high temperature conditions. For example, in some high temperature industrial environments or places with fire risks, it can effectively protect the internal structure of the cable.

[0123] ②Good insulation performance: It can play a good insulation role, prevent current leakage, and ensure the stability of the electrical performance of the cable. Its high insulation resistance can effectively avoid short circuits between conductors inside the cable or between conductors and the outside world, and ensure the safety and reliability of power transmission.

[0124] ③Excellent fire resistance: When exposed to open flames, the calcined mica tape has good fire resistance, is not easy to burn, and can effectively prevent the spread of flames. In addition, there is basically no volatilization of harmful smoke during the combustion process, which can not only buy time for personnel evacuation and fire rescue, but also reduce the harm to the environment and human body when a fire occurs, meeting the fire safety requirements.

[0125] ④ Strong mechanical strength: It has a certain mechanical strength and can withstand the mechanical stress such as stretching, bending, extrusion, etc. that the cable may be subjected to during installation, laying and use. It is not easy to be damaged or broken, ensuring the integrity of the cable structure and thus extending the service life of the cable.

[0126] ⑤Stable chemical properties: It has good chemical stability, is resistant to acid, alkali and corrosion, is not easily corroded by chemical substances, can adapt to various complex environmental conditions, and can maintain its stable performance in some harsh chemical environments, ensuring the normal use of the cable.

[0127] Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrap 1 layer, overlap rate 15%-25%, further improve the high temperature resistance and fire resistance of the cable. The specific advantages are as follows:

[0128] ①Excellent fire resistance: In high temperature environment, ceramic silicone tape can be quickly burned into a ceramic-like hard and complete shell. This ceramic shell can play a good role in flame retardancy, fire resistance, fire prevention and fire isolation, and effectively protect the internal objects. For example, in the event of a fire, it can ensure the smooth flow of the line within a certain period of time, and buy precious time for personnel evacuation and fire rescue. Its fire resistance temperature is usually high, and some ceramic silicone tapes can withstand 550℃-1000℃ or even higher temperatures.

[0129] ②Good insulation performance: Ceramic silicone tape has good electrical insulation performance, can effectively prevent current leakage, ensure the safety and stability of power transmission, and can be used as the insulation layer of wires and cables to ensure the normal operation of electrical equipment.

[0130] ③Excellent mechanical properties: The material itself is soft, elastic, and strong under normal conditions, and has good tensile, bending, and wear resistance. It is not easy to be damaged or broken during installation and use, and can withstand certain mechanical stresses, such as maintaining structural integrity during cable laying and bending.

[0131] ④ Environmental protection and non-toxicity: Ceramic silicone tape usually does not contain harmful substances, such as halogens, heavy metals, etc. The smoke after combustion is low-smoke, halogen-free, phosphorus-free, nitrogen-free, non-toxic, harmless, and friendly to the human body and the environment. In some places with high environmental protection requirements, such as hospitals, schools, shopping malls, etc., it is more appropriate to use ceramic silicone tape.

[0132] ⑤Good high and low temperature resistance: It can work normally in a wide temperature range, and the operating temperature range is generally -70℃~+200℃. It can adapt to high temperature environment, such as being used in some high temperature industrial equipment, and can maintain stable performance in low temperature environment, such as being used in outdoor cables in cold areas.

[0133] ⑥Good moisture-proof and waterproof performance: Compared with some traditional materials such as mica tape, ceramic silicone tape does not absorb water or moisture, and can still maintain good performance in a humid environment. It is not easily affected by moisture and its insulation, fire resistance and other properties are affected, which reduces the risk of leakage caused by moisture penetration, increases product reliability and service life, and reduces maintenance costs.

[0134] ⑦Good processing performance: It can be formed and manufactured through a variety of processing methods, such as calendering, coating, etc., which can meet the needs of different shapes and sizes, and is convenient for making tapes of various specifications or for different application scenarios. In addition, it is not easy to have problems such as sticking to the roller and difficulty in unloading during the processing, which can simplify the production process.

[0135] Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrap one layer, and overlap 20%-30% to prevent moisture from entering the cable and affecting the performance of the cable. The specific advantages are as follows:

[0136] ①High efficiency water blocking performance

[0137] 1. All-round protection: It can effectively block the intrusion of water from two sides, both horizontally and vertically, and provide strict waterproof protection for the cable. Even in harsh humid environments, it can ensure that the inside of the cable is dry and maintain good electrical performance.

[0138] 2. Reduce the risk of failure: Preventing moisture from entering the cable can reduce the probability of insulation degradation, short circuit and other failures caused by moisture, and improve the reliability and stability of cable operation.

[0139] ② Enhance mechanical strength

[0140] 1. Provide additional support: Double-sided water-blocking tape increases the overall strength of the cable, making it more able to withstand external pressure, tension and torsional force during installation, laying and use.

[0141] 2. Reduce damage: Helps protect the conductor and insulation layer inside the cable from mechanical damage and extend the service life of the cable.

[0142] ③Good compatibility

[0143] 1. Coordination with cable materials: It usually has good compatibility with various cable materials, will not have adverse effects on other components of the cable, and ensure the optimization of the overall performance of the cable.

[0144] 2. Easy to process: In the cable production process, the double-sided water-blocking tape is easy to integrate without adding too much process complexity and cost.

[0145] ④Environmentally friendly and sustainable

[0146] 1. Green and environmentally friendly: Many double-sided water-blocking tapes are made of environmentally friendly materials, which are environmentally friendly and meet the requirements of sustainable development.

[0147] 2. Recyclability: After the cable is scrapped, part of the water-blocking tape can be recycled to reduce resource waste and pressure on the environment.

[0148] Ceramic fiber: Use 0.5mm thick ceramic fiber, wrap 1 layer, overlap rate 25%-45%, enhance the fire resistance and heat insulation performance of the cable. The specific advantages are as follows:

[0149] ①Excellent high temperature resistance: It can work stably for a long time in high temperature environment, the continuous use temperature can reach 1000℃, and the short-term use temperature can even reach 1260℃.

[0150] ②Low thermal conductivity: Low thermal conductivity, good thermal insulation performance, can effectively reduce heat transfer and have a good thermal insulation effect.

[0151] ③Good thermal stability: When the temperature changes, the volume and shape change very little, it is not easy to break or be damaged due to thermal expansion and contraction, and can adapt to working conditions of rapid heating and cooling.

[0152] ④Light weight: It is a lightweight material, only 1 / 5-1 / 10 of lightweight refractory materials, which makes it more convenient during installation and use and reduces the load on the supporting structure.

[0153] ⑤ Strong chemical stability: The main chemical component is aluminum silicate, which is a neutral to acidic material. Except for reacting with strong acids and alkalis, it is not corroded by other acids, alkalis, water, oils, and steam, and has good corrosion resistance.

[0154] ⑥Non-toxic, harmless and odorless: It has no toxic side effects on the human body and the environment, and is safe and reliable to use.

[0155] ⑦Good resistance to mechanical vibration: It has certain flexibility and elasticity, can withstand mechanical vibration and impact, and is not easily damaged.

[0156] ⑧Good electrical insulation: Ceramic fiber cloth, tape, packing and other products using alkali-free glass fiber as reinforcement material have higher electrical insulation and high-temperature electrical insulation than glass fiber, and can be used for insulation of high-temperature electrical appliances.

[0157] ⑨Good processing performance: It can be processed into various shapes and sizes according to needs, such as blankets, felt, boards, paper, ropes, belts and other special-shaped products to meet the needs of different application scenarios.

[0158] ⑩Significant energy-saving effect: It can effectively reduce heat loss and improve energy utilization efficiency. When used in industrial furnaces and other equipment, it can save 20%-30% energy.

[0159] Dense glass fiber tape: Use 0.2mm thick dense glass fiber tape, wrap 1 layer, overlap rate 10%-15%, improve the mechanical strength and corrosion resistance of the cable. The specific advantages are as follows:

[0160] ①Excellent physical properties

[0161] 1. High strength: Glass fiber itself has high strength, and dense glass fiber tape can provide reliable mechanical support and protection for the product.

[0162] 2. Good dimensional stability: Under different temperature and humidity conditions, it maintains a relatively stable size and is not easy to deform, ensuring accuracy and reliability during use.

[0163] ②Good insulation performance

[0164] 1. High insulation resistance: It can effectively prevent the passage of current, play a good insulating role, and ensure the safe operation of electrical equipment.

[0165] 2. Strong arc resistance: When abnormal conditions such as arcs occur, it can withstand a certain arc impact without being easily damaged, thereby improving the safety of the electrical system.

[0166] ③High temperature resistance

[0167] 1. Can be used at higher temperatures: Generally, it can withstand a certain range of high temperatures and maintain stable performance in high temperature environments, making it suitable for various high temperature working scenarios.

[0168] 2. Flame retardancy: Glass fiber itself has certain flame retardant properties, which reduces the risk of fire.

[0169] ④Good chemical stability

[0170] 1. Corrosion resistance: It has good tolerance to acids, alkalis, organic solvents, etc., is not easily corroded by chemical substances, and prolongs its service life.

[0171] 2. Aging resistance: During long-term use, it is not easy to age and deteriorate due to natural environmental factors, and its performance is stable and long-lasting.

[0172] ⑤Environmental protection and sustainability

[0173] 1. Non-toxic and harmless: no toxic side effects on human body and environment, safe to use.

[0174] 2. Recyclable: Fiberglass materials can be recycled and reused to a certain extent, reducing resource waste and impact on the environment.

[0175] ⑥Easy to process and use

[0176] 1. Good softness: It can be cut, wound and processed as needed, making it convenient to use on products of different shapes and sizes.

[0177] 2. Easy installation: No complicated tools and processes are required, reducing installation costs and time.

[0178] First copper sheath: It uses 0.5mm thick copper strip with 1.5mm corrugation depth, providing good grounding protection and electromagnetic shielding performance. The specific advantages are as follows:

[0179] ① High temperature resistance: Copper has a high melting point of about 1083°C. In general fire scenes, the temperature is difficult to reach the melting point of copper. For example, the highest temperature at the fire scene of ordinary civil buildings is usually below 1000°C, so the copper sheath can maintain the integrity of the structure in such an environment, continue to provide protection for the conductor inside the cable, prevent the conductor from being damaged by high temperature, and ensure that the cable can still maintain normal power transmission for a certain period of time during the fire.

[0180] ② Not easy to burn: Copper itself is not a flammable substance. Under the action of fire, the copper sheath will not burn as easily as some organic materials, thus avoiding the spread of fire or further damage to the cable line caused by the burning of the sheath, and helping to control the scope and extent of the fire.

[0181] ③ High mechanical strength: In a fire, the cable may be subjected to various external forces, such as the collapse of buildings, the impact of fire water, etc. The copper sheath has high mechanical strength, which can resist the impact and extrusion of these external forces, protect the internal conductor and insulation layer from damage, and ensure that the cable can still maintain its basic physical structure and electrical performance in a harsh fire environment.

[0182] ④Good stability: Copper has good chemical stability at high temperatures and is not prone to chemical reactions or harmful substances. This means that even under high temperature conditions of fire, the copper sheath will not release toxic gases or other substances that are harmful to the environment and human body, which meets the requirements of fire safety and provides a relatively safe environment for personnel evacuation and rescue work at the fire scene.

[0183] Glass powder: A layer of glass powder is filled outside the first copper sheath. The thickness of the glass powder is 1.8mm. It is filled inside the cable to enhance the fire resistance of the cable. The specific advantages are as follows:

[0184] ①Excellent physical properties

[0185] 1. High hardness: Glass powder can significantly improve the hardness of the material and enhance the wear resistance and scratch resistance of the product. For example, after adding glass powder to the coating, the surface of the coated cable can be made harder and less likely to be scratched, thus extending the service life of the coating.

[0186] 2. Good stability: It has good thermal stability and chemical stability. It is not easy to deform or decompose in high temperature environment, and can withstand certain temperature changes while maintaining stable performance. At the same time, it is resistant to most chemical substances and is not easily corroded.

[0187] ② Enhance material performance

[0188] 1. Improve strength: Adding glass powder to materials such as plastics and rubber can enhance the mechanical strength of the material and make it more able to withstand external forces. For example, adding glass powder to engineering plastics can improve the tensile strength, bending strength and other mechanical properties of the plastic.

[0189] 2. Improve wear resistance: Due to its high hardness, it can effectively improve the wear resistance of materials. In some occasions with high requirements for wear resistance, such as floor coatings, industrial coatings, etc., the application of glass powder can greatly improve the wear resistance of the product.

[0190] 3. Enhanced insulation: It has good insulation properties and can be used in electrical insulation materials to improve the insulation strength and arc resistance of the materials.

[0191] ③Environmental protection and safety

[0192] 1. Non-toxic and harmless: Glass powder is generally made of natural minerals or environmentally friendly materials, which is non-toxic and tasteless, harmless to the human body and the environment. It will not release harmful substances during use and meets environmental protection requirements.

[0193] 2. Recyclable: Glass powder can be used as a recyclable material. If there is excess or waste glass powder in the production process, it can be recycled and reused to reduce resource waste.

[0194] Second copper sheath: It uses 0.8mm thick copper strip, 1.0mm corrugation depth, and double copper sheath design to further improve the fire resistance and mechanical strength of the cable. The specific advantages are as follows:

[0195] ①Protective effect

[0196] 1. Mechanical protection: The copper sheath provides a solid shell for the conductor and insulation layer inside the cable, which can effectively resist external mechanical pressure, impact and wear. Whether it is dragging, bending during cable laying, or extrusion during use, the copper sheath can play a good protective role and prevent damage to the internal structure.

[0197] 2. Moisture-proof and waterproof: Copper has good sealing properties and can prevent moisture and humidity from invading the interior of the cable. In humid environments, such as underground and underwater, the copper sheath can ensure that the insulation performance of the cable is not affected, avoiding short circuits, leakage and other faults caused by moisture, greatly improving the reliability and service life of the cable.

[0198] ②Electrical performance

[0199] 1. Good conductivity: Although the main conductive part of the cable is the internal conductor, the copper sheath also has a certain conductivity. In some special cases, such as when the cable fails or the grounding is poor, the copper sheath can serve as an auxiliary conductive channel to help the current return to the power source safely and reduce the risk of electric shock.

[0200] 2. Shielding effect: The copper sheath can effectively shield external electromagnetic interference, prevent external electromagnetic fields from interfering with the internal signals of the cable, and ensure the quality and stability of the cable transmission signal. At the same time, it can also reduce the electromagnetic radiation of the internal signal of the cable to the outside world and reduce the impact on surrounding electronic equipment.

[0201] ③Safety and environmental protection

[0202] 1. Fireproof performance: Copper has a high melting point. In the event of a fire, the copper sheath can maintain the integrity of the cable for a certain period of time, delay the spread of the fire, and buy precious time for personnel evacuation and fire rescue. At the same time, the copper sheath will not release toxic and harmful gases during the combustion process, which is relatively safe and environmentally friendly.

[0203] 2. Grounding protection: The copper sheath can serve as a good grounding conductor to ensure that the grounding of the cable system is safe and reliable. It can promptly conduct leakage current and fault current to the earth, avoid the risk of electric shock and equipment damage, and ensure the safety of people and equipment.

[0204] The following are the specific structures of the design embodiments and comparative examples of the present invention, wherein structure 1 is an embodiment of the present invention, and structures 2 to 8 are comparative examples of the present invention.

[0205] The glass powder used below includes the following components by weight: 25 parts of silicate, including 8 parts of orthoclase, 13 parts of talc, and 4 parts of asbestos; 13 parts of borate, including 4 parts of borax, 5 parts of borax, and 4 parts of colemanite; 20 parts of oxides, including 9 parts of titanium dioxide, 8 parts of manganese dioxide, and 3 parts of ferric oxide.

[0206] Structure 1: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped in 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped in 1 layer, overlapping rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped in 1 layer, overlapping rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped in 1 layer, overlapping rate 25%-45%, Dense glass fiber tape: 0.2mm thick dense glass fiber tape, wrapped in 1 layer, overlap rate 10%-15%, copper sheath: 0.5mm thick copper tape, embossing depth 1.5mm, glass powder: fill a layer of glass powder outside the first copper sheath, glass powder thickness 1.8mm, copper sheath: 0.8mm thick copper tape, embossing depth 1.0mm, sample outer diameter 24.5mm, test results total calorific value PCS1.4MJ / kg a .

[0207] ②Structure 2: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped in 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped in 1 layer, overlapping rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped in 1 layer, overlapping rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped in 1 layer, overlapping rate 25%-45%, Dense glass fiber tape: Use thick 0.2mm dense glass fiber tape, wrapped in 1 layer, overlap rate 10%-15%, insulation: XLPE, thickness 1.5mm, copper sheath: 0.5mm thick copper tape, embossing depth 1.5mm, glass powder: a layer of glass powder is filled outside the first copper sheath, the glass powder thickness is 1.8mm, copper sheath: 0.8mm thick copper tape, embossing depth 1.0mm, the sample outer diameter is 28.4mm, the test result total calorific value PCS3.2MJ / kg a .

[0208] ③Structure 3: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped in 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped in 1 layer, overlapping rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped in 1 layer, overlapping rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped in 1 layer, overlapping rate 25%-45%, Insulation: Use halogen-free low-smoke insulation Edge, thickness is 1.5mm, copper sheath: 0.5mm thick copper belt, embossing depth is 1.5mm, glass powder: fill a layer of glass powder outside the first copper sheath, glass powder thickness is 1.8mm, dense glass fiber tape: 0.2mm thick dense glass fiber tape, wrapped 1 layer, overlap rate is 10%-15%, copper sheath: 0.8mm thick copper belt, embossing depth is 1.0mm, the sample outer diameter is 28.6mm, the test result total calorific value is PCS3.4MJ / kg a .

[0209] ④Structure 4: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped 5 layers, Insulation: Use XLPE, thickness 1.5mm, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped 1 layer, overlap rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped 1 layer, overlap rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped 1 layer, weight The overlap rate is 25%-45%. Dense glass fiber tape: 0.2mm thick dense glass fiber tape is used, wrapped in 1 layer, the overlap rate is 10%-15%. Copper sheath: 0.5mm thick copper tape is used, and the embossing depth is 1.5mm. Glass powder: a layer of glass powder is filled outside the first copper sheath, and the thickness of the glass powder is 1.8mm. Copper sheath: 0.8mm thick copper tape is used, and the embossing depth is 1.0mm. The outer diameter of the sample is 29mm. The total calorific value of the test result is PCS3.5MJ / kg a .

[0210] ⑤Structure 5: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped in 5 layers, Insulation: Use XLPE, thickness 1.5mm, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped in 1 layer, overlap rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped in 1 layer, overlap rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped 1 layer, overlap rate is 25%-45%, dense glass fiber tape: use 0.2mm thick dense glass fiber tape, wrap 1 layer, overlap rate is 10%-15%, insulation: use halogen-free low-smoke insulation, thickness is 1.5mm, glass powder: fill a layer of glass powder outside the first copper sheath, the thickness of the glass powder is 1.8mm, copper sheath: use 0.8mm thick copper tape, embossing depth is 1.0mm, the outer diameter of the sample is 27mm, the total calorific value of the test result is PCS3.7MJ / kg a .

[0211] ⑥Structure 6: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped 1 layer, overlap rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped 1 layer, overlap rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped 1 layer, overlap rate 25%-45%, Dense glass fiber tape: Use 0.2mm thick dense glass fiber tape, wrapped 1 layer, overlap rate 10%-15%, Glass powder: Fill a layer of glass powder outside the first copper sheath, the glass powder thickness is 1.8mm, Copper sheath: Use 0.8mm thick copper tape, corrugation depth is 1.0mm, the outer diameter of the sample is 23.2mm, the test result is total calorific value PCS2.1MJ / kg a .

[0212] ⑦Structure 7: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped 1 layer, overlap rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped 1 layer, overlap rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped 1 layer, overlap rate 25%-45%, Dense glass fiber tape: Use 0.2mm thick dense glass fiber tape, wrapped 1 layer, overlap rate 10%-15%, Insulation: Use XLPE, thickness 1.5mm, Glass powder: Fill a layer of glass powder outside the first copper sheath, glass powder thickness 1.8mm, Copper sheath: Use 0.8mm thick copper tape, corrugation depth 1.0mm, sample outer diameter 26.2mm, test results total calorific value PCS2.6MJ / kg a .

[0213] ⑧Structure 8: Conductor: Use special-shaped single crystal copper wire, Forged mica tape: Use 0.14mm thick forged mica tape, wrapped 5 layers, Ceramic silicone tape: Use 0.5mm thick ceramic silicone tape, wrapped 1 layer, overlap rate 15%-25%, Double-sided water-blocking tape: Use 0.3mm thick double-sided water-blocking tape, wrapped 1 layer, overlap rate 20%-30%, Ceramic fiber: Use 0.5mm thick ceramic fiber, wrapped 1 layer, overlap rate 25%-45%, Dense glass fiber tape: Use 0.2mm thick dense glass fiber tape, wrapped 1 layer, overlap rate 10%-15%, Copper sheath: Use 0.8mm thick copper tape, corrugation depth 1.0mm, sample outer diameter 20.2mm, test results Total calorific value PCS4.3MJ / kg a .

[0214] Table 1 Total calorific value test results of embodiments and comparative examples

[0215]

[0216] It can be seen from the test results in Table 1 that, under the test requirement of total calorific value PCS≤2.0MJ / kga, after multiple verifications, only embodiment structure 1 passed the test, and its test result was total calorific value PCS≤1.4MJ / kga, and the remaining structures failed the test. At the same time, in the structures developed in the past, there are few stable and qualified materials that can support non-combustible (Grade A) performance.

[0217] It can be seen from the data of the embodiment structure 1 and the comparative structure 8 of the present invention that glass powder plays a vital role in the manufacture of non-combustible cables. Glass powder gives non-combustible cables excellent flame retardant properties. When the cable is facing a fire risk, the glass powder can effectively prevent the spread of the fire. Its special chemical composition and structure make the cable difficult to burn in a high temperature environment, greatly reducing the possibility and degree of harm of the fire. The non-combustible cable containing a glass powder structure fully meets the standard requirements. The addition of glass powder ensures that the cable meets or even exceeds the relevant standards in various performance indicators. Whether it is electrical performance, mechanical strength or fire resistance, it has been significantly improved. The stability of glass powder is extremely high. It will not deteriorate in performance over time, can maintain the non-combustible characteristics of the cable for a long time, and provides a lasting guarantee for the safe operation of the cable. It plays a key role in non-combustible cables and is an important factor in achieving high performance, high safety and compliance with standard requirements for non-combustible cables.

[0218] Table 2 Comparison of key performances of non-flammable cables

[0219]

[0220] The present invention takes the conductor as the core, and sequentially wraps the calcined mica tape, ceramic silicone tape, double-sided water-blocking tape, ceramic fiber, dense glass fiber tape, copper sheath, glass powder and copper sheath. The synergistic effect of various protective materials, the calcined mica tape, ceramic silicone tape, ceramic fiber and dense glass fiber tape enhance the fire resistance of the cable; the double-sided water-blocking tape can prevent moisture intrusion; the copper sheath plays a good mechanical protection and grounding role; the glass powder can further improve the flame retardant performance of the cable. This non-combustible cable has significant advantages in fire prevention, waterproofing, mechanical strength and other aspects, and is suitable for places with high safety requirements.

[0221] The non-combustible cables of structure 1 in Table 1 and Table 2 have been verified many times, and it has been concluded that the reasonable use of good oxygen-isolating and heat-insulating materials can lead to a good conclusion, which can fully meet the requirements of non-combustible Class A and ensure reliable continuous production.

[0222] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A non-combustible cable, characterized in that: Its structure is a multi-layer cable structure, with the outer layer wrapping the inner layer. The cable structure is composed of a conductor, a calcined mica tape, a ceramic silicone tape, a double-sided water-blocking tape, ceramic fiber, a dense glass fiber tape, a first copper sheath, glass powder, and a second copper sheath from the inside to the outside. The cross-sectional shape of the cable is circular. The glass powder includes the following components by weight: 20 to 25 parts of silicate, 10 to 13 parts of borate, and 18 to 20 parts of oxide.

2. A non-combustible cable according to claim 1, characterized in that: The conductor is a round conductor formed by twisting and pressing a plurality of special-shaped single-crystal copper wires; the thickness of the calcined mica tape is 0.14 mm, and it is wrapped in 5 layers on the outer layer of the conductor, with an overlap rate of 15%-25% for each layer; the thickness of the ceramic silicone tape is 0.5 mm, and it is wrapped in 1 layer on the outer layer of the calcined mica tape, with an overlap rate of 15%-25%; the thickness of the double-sided water-blocking tape is 0.3 mm, and it is wrapped in 1 layer on the outer layer of the ceramic silicone tape, with an overlap rate of 20%-30%.

3. A non-combustible cable according to claim 2, characterized in that: The thickness of the ceramic fiber is 0.5mm, and one layer of it is wrapped around the outer layer of the double-sided water-blocking tape, with an overlap rate of 25%-45%; the thickness of the dense glass fiber tape is 0.2mm, and one layer of it is wrapped around the outer layer of the ceramic fiber, with an overlap rate of 10%-15%; the thickness of the first copper sheath is 0.5mm, and the embossing depth is 1.5mm, and it is arranged on the outer layer of the dense glass fiber tape; the thickness of the glass powder is 1.8mm±0.10mm, and the glass powder is filled in one layer on the outer layer of the first copper sheath; the thickness of the second copper sheath is 0.8mm, and the embossing depth is 1.0mm, and it is arranged on the outer layer of the glass powder.

4. A non-combustible cable according to claim 3, characterized in that: The silicate is one or more of orthoclase, talc, and asbestos; the borate is one or more of borax, borax, and colemanite; the oxide is one or more of titanium dioxide, manganese dioxide, and ferric oxide.

5. A method for preparing a non-combustible cable as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: A. Conductor preparation: Use special-shaped single crystal copper wire, and twist and compress multiple special-shaped single crystal copper wires to form a round conductor; B. Wrapping of each layer of materials: In the aforementioned order, wrap the calcined mica tape, ceramic silicone tape, double-sided water-blocking tape, ceramic fiber, dense glass fiber tape and the first copper sheath tightly on the outer layer of the conductor. Obtain semi-finished product B; C. Filling of glass powder: filling the outer layer of the semi-finished product B obtained in step B with glass powder evenly to obtain a semi-finished product C; D. Cable molding: a second copper sheath is provided on the outer layer of the semi-finished product C, and the semi-finished product C is wrapped and molded to obtain a finished cable; The preparation method of the glass powder is as follows: ① Raw material preparation: prepare the required raw materials, including silicates, borates, and oxides; ② Ingredient mixing: Accurately weigh various raw materials according to the formula ratio, put the weighed raw materials into the mixing equipment, stir and mix them thoroughly to form a mixture; ③ High temperature melting: Put the mixture into a high temperature furnace and heat it to above 1000℃ to completely melt the mixture to obtain molten glass liquid; ④ Water quenching cooling: Take the molten glass liquid out of the furnace and quickly pour it into water for water quenching; ⑤ Grinding and crushing: Take out the glass pieces after water quenching and put them into the grinding equipment for grinding; ⑥ Screening and grading: The ground glass powder can be screened to obtain glass powder of the required particle size.

6. The method for preparing a non-combustible cable according to claim 5, characterized in that: In step C, the glass powder is extruded by an extruder so that it can be evenly filled in the outer layer of the semi-finished product B. The specific steps of extruding the glass powder are as follows: (1) Raw material preparation: Add the manufactured glass powder into the twin-screw extruder; (2) Extruder preheating: Heat each area of ​​the extruder to 950°C to ensure that the glass powder can be melted and extruded smoothly; (3) Feeding: Feed the mixed raw materials into the hopper of the extruder through a feeder; (4) Melt extrusion: The mixed raw materials are gradually melted and pushed toward the die head under the action of the extruder screw, shear force and heat; (5) Molding: The molten glass powder passes through the die of the die head and is evenly extruded on the outer layer of the semi-finished product B to form the desired shape and size; (6) Cooling and shaping: The extruded product is quickly cooled by a cooling water tank device to solidify and shape it; (7) Traction: Use a traction device to pull the cooled and shaped cable product out of the extruder to obtain a semi-finished product C.

7. A method for preparing a non-combustible cable according to claim 5 or 6, characterized in that: The calcined mica tape is wrapped around the outer layer of the conductor using a 10-head horizontal wrapping machine, and the tension of the calcined mica tape is stably controlled by a tension regulator during the wrapping process; the ceramic silicone tape, double-sided water-blocking tape, ceramic fiber, and dense glass fiber tape are wrapped using a 10-head horizontal wrapping machine; the first copper sheath and the second copper sheath are produced using imported copper sheath argon arc welding equipment.

8. A method for preparing a non-combustible cable according to claim 5 or 6, characterized in that: During the high temperature melting process in step ③, it is necessary to control the melting temperature to be not less than 1200°C, the time to be not less than 12 minutes, and the atmosphere temperature to be not less than 600°C.

9. A method for preparing a non-combustible cable according to claim 5 or 6, characterized in that: In the screening and grading in step ⑥, the ground glass powder is screened and glass powder with a particle size of 0.25 mm-0.30 mm is selected.

10. The method for preparing a non-combustible cable according to claim 6, characterized in that: The glass powder filled in the outer layer of the semi-finished product B has a stirring pressure of 14 bar and a viscosity of 690 Pa·s to 900 Pa·s before filling.

Citation Information

Patent Citations

  • Safe and flexible fire resistant cable

    CN104700933A

  • Ceramic fire-resistant belt and preparation method thereof

    CN108417309A

  • Fireproof DC trailing cable used for rail transit

    CN204480713U

  • B1-level power cable

    CN209401350U

  • Flexible environmentfriendly silicone rubber hightemperatureresistant waterproof flameretardant cable

    CN213635474U